2019
DOI: 10.3892/ijmm.2019.4170
|View full text |Cite
|
Sign up to set email alerts
|

DHA protects PC12 cells against oxidative stress and apoptotic signals through the activation of the NFE2L2/HO-1 axis

Abstract: docosahexaenoic acid (dHA) is an omega-3 polyunsaturated fatty acid, derived mainly from fish oil. It is well known that DHA is present in high concentrations in nervous tissue and plays an important role in brain development and neuroprotection. However, the molecular mechanisms underlying its role remain to be fully elucidated. In this study, to enhance our understanding of the pathophysiological role of DHA, we investigated the possible neuroprotective mechanisms of action of dHA against hydrogen peroxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 40 publications
5
35
0
Order By: Relevance
“…As a crucial organ, the liver is easily harmed by oxidative stress. Many studies have indicated that DHA up-regulates the expression of HO-1 or SOD to relieve oxidative stress in neuronal cells, and is involved in the treatment of a variety of neurodegenerative diseases [ 24 ]. However, its antioxidant function in hepatocytes has been less reported.…”
Section: Discussionmentioning
confidence: 99%
“…As a crucial organ, the liver is easily harmed by oxidative stress. Many studies have indicated that DHA up-regulates the expression of HO-1 or SOD to relieve oxidative stress in neuronal cells, and is involved in the treatment of a variety of neurodegenerative diseases [ 24 ]. However, its antioxidant function in hepatocytes has been less reported.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest a dual antioxidant and anti‐apoptotic role for DHA. Furthermore, the protective effect of DHA on oxidative damage by hydrogen peroxide (H 2 O 2 ) was demonstrated using the rat pheochromocytoma cell line PC12 (Clementi, Lazzarino, Sampaolese, Brancato, & Tringali, 2019). DHA supplementation prevented the loss of viability; ROS loss was induced after 24 hr exposure to H 2 O 2 .…”
Section: Inhibitory Effect Of Dha On Nerve Cell Injurymentioning
confidence: 99%
“…Taken together, these results suggest a dual antioxidant and anti-apoptotic role for DHA. Furthermore, the protective effect of DHA on oxidative damage by hydrogen peroxide (H 2 O 2 ) was demonstrated using the rat pheochromocytoma cell line PC12 (Clementi, Lazzarino, Sampaolese, Brancato, & Tringali, 2019 Similarly, the inhibitory effect of DHA on oxidative stress induced by H 2 O 2 and tert-butyl hydroperoxide was shown in PC12 cells (Che et al, 2018). On the other hand, it was shown that the addition of DHA-PS significantly induced the survival rate of PC12 and inhibited leakage of lactate dehydrogenase, and markedly suppressed the induction of apoptosis.…”
Section: Inhib Itory Effec T Of Dha On Nerve Cell Inj Urymentioning
confidence: 99%
“…Docosahexaenoic acid (DHA) is an omega-3 fatty acid mainly found in fish oil which possesses anti-oxidative ( 100 ), anti-inflammatory ( 101 , 102 ), and neuroprotective effects ( 103 ). DHA has been shown to reduce the level of endoplasmic reticulum stress and to inhibit abnormal protein accumulation [such as amyloid precursor protein (APP) and phospho-Tau proteins] within the brain following TBI ( 104 ).…”
Section: Traumatic Brain Injurymentioning
confidence: 99%